2017
DOI: 10.1038/nn.4562
|View full text |Cite
|
Sign up to set email alerts
|

Cortical gamma band synchronization through somatostatin interneurons

Abstract: Gamma band rhythms may synchronize distributed cell assemblies to facilitate information transfer within and across brain areas, yet their underlying mechanisms remain hotly debated. Most circuit models pose that soma-targeting parvalbumin (PV) positive GABAergic neurons are the essential inhibitory neuron subtype necessary for gamma rhythms. Using cell-type specific optogenetic manipulations in behaving animals, we show that dendrite-targeting somatostatin (SOM) interneurons are critical for a visually induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

56
389
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 349 publications
(446 citation statements)
references
References 65 publications
56
389
1
Order By: Relevance
“…Control trials were interleaved with trials in which the cortex was illuminated with an optic fiber coupled to a red LED. Under identical experimental conditions, extracellular recording from SOM cells revealed a 67±8% decrease in SOM firing for the largest stimulus size (Veit et al, 2017). Consistent with the reduced surround suppression observed during their inactivation (~30% decrease for ~57% suppression of SOM firing) (Adesnik et al, 2012), optogenetic suppression of SOM cells substantially increased both visually evoked E and I (E: p < 0.0005, I: p < 0.005, two-way-ANOVA, n = 8, Figure 8B,C), but did not eliminate the size-dependent decrement in the E/I ratio (p > 0.05, two-way-ANOVA, Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Control trials were interleaved with trials in which the cortex was illuminated with an optic fiber coupled to a red LED. Under identical experimental conditions, extracellular recording from SOM cells revealed a 67±8% decrease in SOM firing for the largest stimulus size (Veit et al, 2017). Consistent with the reduced surround suppression observed during their inactivation (~30% decrease for ~57% suppression of SOM firing) (Adesnik et al, 2012), optogenetic suppression of SOM cells substantially increased both visually evoked E and I (E: p < 0.0005, I: p < 0.005, two-way-ANOVA, n = 8, Figure 8B,C), but did not eliminate the size-dependent decrement in the E/I ratio (p > 0.05, two-way-ANOVA, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Superficially, the increase in I seems paradoxical, as the direct inhibition from SOM cells should be reduced. However, this paradoxical effect is precisely a core prediction of the ISN regime (Litwin-Kumar et al, 2016; Rubin et al, 2015; Tsodyks et al, 1997); when SOM cells are suppressed, PV cells firing rates substantially increase (Veit et al, 2017). In the ISN model, the increased activity of PV cells is a result of increased drive from L2/3 excitatory neurons (which are net disinhibited).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Veit et al . ), we hypothesized that GAERS could present a layer‐specific increase of interneurons density, especially of PV+ or SOM+ cells. Recent studies indicated modifications of GABAergic interneurons densities in models of genetic epilepsy that further support our hypothesis (Wimmer et al .…”
Section: Resultsmentioning
confidence: 99%
“…; Buzsáki & Wang, ; Veit et al . ), an increased number of these interneurons could explain the augmented gamma power in GAERS that not only favours SWDs, but also may alter sensory coding. A recent study showed no difference in terms of GABA+ interneurons in the S1Bf of GAERS (Bombardi et al .…”
Section: Discussionmentioning
confidence: 99%